ANALISIS PIUTANG USAHA PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) DI AIRMADIDI KABUPATEN MINAHASA UTARA - Lahengking, Erlita Mentari; Elim, Inggriani; Pusung, Rudy (Universitas Sam Ratulangi, 2017)
Accounts receivable of a company generally represent the bulk of current assets and the largest part of the total assets of the company. Therefore, good accounting and accounting management of these accounts receivable is very important to be applied. This study aims to determine the management and recording of accounting receivables and accounts receivable analysis applied to PDAM Kabupaten Minahasa Utara. The object of this research is PDAM Kabupaten Minahasa Utara. The method used in this study is descriptive method is a method used to draw or analyze, comparing a research result but not used to make wider conclusions. Sources of data used are secondary data that is financial report data PDAM Kabupaten Minahasa Utara in the period 2013 until the period 2015 obtained from PDAM Kabupaten Minahasa Utara. The results showed that PDAM Kabupaten Minahasa Utara has applied SAK ETAP on accounting management and accounting records but there are still some provisions that have not been implemented PDAM Kabupaten Minahasa Utara in accordance with SAK ETAP so there are many bad debts. The result of analysis of Receivable Turn Over (RTO) and Average Collection Period (ACP) ratio shows that receivable turnover and receivable collection do not match with the target company.Keywords : Accounts Receivable, Accounts Receivable Turnover, Receivables Collection, SAK-ETAP